Study on electrcal power generation system by harnessing household garbage (case study UTM Campus Johor Bahru) - Ahmed Abubakar Elwan, 1976-; Yanuar Z. Arief, supervisor; Fakulti Kejuruteraan Elektrik (2013)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2013